Ships leaving a port under emergency conditions - Paulauskas, Vytautas; Lukauskas, Valdas; Plačiene, Birute; Barzdžiukas, Raimondas (Transport, 2012)
Emergency conditions in a port request special precaution measures taken by ships when in the majority of cases they necessitate leaving port waters in the shortest time. Good management, awareness and timely actions can help with avoiding difficulties encountered by ships under emergency conditions at ports. The conducted research suggested in the article has been based on investigation into ship maneuverability considering complicated weather conditions, theoretical methods for the feasibility of ship maneuverability referring to difficult conditions, experimental tests using the calibrated Simulator and evaluation of real ships under similar conditions. The results of the presented research could be used for analyzing the situation in different ports with different ships regarding practical preparation for vessels to leave the port under emergency conditions without any delay.First Published Online: 21 Dec 2012